Cloud-based data mapper (CDM): application for monitoring dry deposition of reactive nitrogen - Kharol, Shailesh K.; Prapavessis, Cameron; Shephard, Mark W.; McLinden, Chris A.; Griffin, Debora (Frontiers in Environmental Science, 2023)
Spatiotemporal monitoring of reactive nitrogen atmospheric deposition is essential for understanding its impact on sensitive ecosystems and quantifying cumulative efforts. However, the sparsity of direct surface flux measurements combined with barriers in dissemination are major limiting factors in providing this information to decision makers and non-experts in a timely manner. This work addresses both aspects of this information gap by, 1) utilizing satellite-derived reactive nitrogen dry deposition data products that can be used by decision-makers to supplement the sparse direct surface flux measurements and 2) fill in measurement gaps. Therefore, we have developed a Reactive Nitrogen Flux Mapper (RNFM) component of the interactive Cloud-based Data Mapper (CDM) for providing easy access of satellite-derived reactive nitrogen (defined here as nitrogen dioxide (NO2) and ammonia (NH3)) dry deposition flux spatial maps/data to decision-makers/stakeholders over North America. The RNFM component of CDM has a Graphical User Interface (GUI) that allows users to specify the geographical regions and time periods for computing the average fluxes on the fly using an integrated cloud-based computing platform. The CDM architecture is flexible and can be upgraded in the future to take advantage of upstream satellite data directly on cloud platforms to provide results in near real-time.